REMORA 94. Analyse des résultats de la seconde année du réseau de suivi de la croissance de l'huître creuse sur les côtes françaises - Goyard, Emmanuel (1996)
The Aquaculture Resources department Mollusc Network (REMORA ) has been monitoring in 1994 like in 1993 the growth of homogeneous batches of Crassostrea gigas (initially 18 months old, same origin, same history, same size) in the main French production areas. The monitored parameters deal with growth, morphology, survival, composition and parasite infestations. The comparison between two rearing conditions (traditional bags versus wooden plate to which individuals were stuck) demonstrated like in 1993 improved growth rate (which could also be explained by the lower local density) and a tendency for the oysters to become wider on plates (which is probably related to the absence of shell erosion). Major regional characteristics are revealed by the analysis, especially in terms of macroscopic composition, morphology and mortality. But regional differences for growth seasonality are no more obvious in 1994. Meteorological conditions could explain this uniformisation of growth rhythms, better growth and higher mortality in 1994. This study confirms REMORA as a potential tool for developing global biomodelisations. Comme en 1993, le REseau MOIlusque du département Ressources Aquacoles (REMORA) effectue en 1994 le suivi trimestriel de lots homogènes d'huîtres Crassostrea gigas (initialement âgées de 18 mois, même origine, même historique, même calibre) sur l'ensemble des principaux bassins ostréicoles français. Les paramètres relevés concernent la croissance, la morphologie, la survie, la composition et les infestations parasitaires. La comparaison de deux supports d'élevage (poche traditionnelle et plaque de bois où les individus sont collés) met en évidence sur les plaques une tendance déjà observée en 1993 à l'élargissement, probablement liée à l'absence d'érosion de la coquille, et une meilleure croissance pondérale, qui pourrait aussi s'expliquer par une densité locale d'élevage plus faible. De fortes particularités régionales déjà relevées en 93 apparaissent, en particulier en terme de composition ...